2015
DOI: 10.1109/tciaig.2015.2466240
|View full text |Cite
|
Sign up to set email alerts
|

Thinking Style and Team Competition Game Performance and Enjoyment

Abstract: Almost all current matchmaking systems for team competition games based on player skill ratings contain algorithms designed to create teams consisting of players at similar skill levels. However, these systems overlook the important factor of playing style. In this paper, we analyze how playing style affects enjoyment in team competition games, using a mix of Sternberg's thinking style theory and individual histories in the form of statistics from previous matches to categorize League of Legend (LoL) players. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…Additionally, it was found that the successful teams in LoL were those that showed the highest scores on the Transactive Memory System Scale, which measures a group's ability to learn, remember, and communicate knowledge relevant to the group (i.e., shared knowledge; Kahn & Williams, 2016). Moreover, Wang, Yang, and Sun (2015) found that those teams that possessed at least one player with a global-liberal playing style, that is, a player who assisted teammates (i.e., collaborative style), had significantly higher win rates than teams without this type of player.…”
Section: Expertise Differences In Esports Performancementioning
confidence: 99%
“…Additionally, it was found that the successful teams in LoL were those that showed the highest scores on the Transactive Memory System Scale, which measures a group's ability to learn, remember, and communicate knowledge relevant to the group (i.e., shared knowledge; Kahn & Williams, 2016). Moreover, Wang, Yang, and Sun (2015) found that those teams that possessed at least one player with a global-liberal playing style, that is, a player who assisted teammates (i.e., collaborative style), had significantly higher win rates than teams without this type of player.…”
Section: Expertise Differences In Esports Performancementioning
confidence: 99%
“…A limitation commonly mentioned in research is how to introduce into the models the synergies that must exist between players of the same team. Related to this question the category of team composition was created for those papers that seek objectives related to the roles of each player within a team [6] [50], the analysis of player behavior in the composition of a team [7] A total of 45 different independent variables were identified in the works within this category. Table 8 presents those used in more than one research.…”
Section: Team Compositionmentioning
confidence: 99%
“…Forecasting focus towards the predictions of the future based past and present data [3,14]. The two terms are focussed on the forecasting are risk and uncertainty.…”
Section: Forecastingmentioning
confidence: 99%